Determinasi Komitmen Organisasi: Studi pada RSIA Bunda Fathia Purwakarta - Mohammad Farid Ghazali; Nenny Hendajany; Etty Sofia Mariati Asnar (MES Bogor, 2026)
This study aims to examine the role of job satisfaction in mediating the relationship between transformational leadership and the work environment on organizational commitment at RSIA Bunda Fathia Purwakarta. The research is grounded in the importance of effective leadership and a supportive work environment in enhancing organizational commitment, which in turn affects employee performance and retention. A quantitative approach was employed through a survey of 275 employees. Data were analyzed using Structural Equation Modeling (SEM) with LISREL 8.8. The results indicate that transformational leadership has a significant positive effect on job satisfaction (β = 0.299; T = 4.753) and organizational commitment (β = 0.216; T = 3.387). The work environment also shows a significant positive effect on job satisfaction (β = 0.209; T = 3.442) and organizational commitment (β = 0.197; T = 3.199). Furthermore, job satisfaction significantly influences organizational commitment (β = 0.251; T = 3.786) and mediates the relationship between transformational leadership (β = 0.075; T = 3.064) and the work environment (β = 0.052; T = 2.611) with organizational commitment. The model explains 20.8% of the variance in organizational commitment. The findings highlight that strengthening organizational commitment requires the implementation of transformational leadership and the creation of a conducive work environment, with job satisfaction serving as a crucial mediating factor.